Variability and trends in the potential vorticity (PV)-gradient dynamical tropopause - K. Turhal; K. Turhal; F. Plöger; F. Plöger; J. Clemens; J. Clemens; T. Birner; T. Birner; F. Weyland; P. Konopka; P. Hoor (Atmospheric Chemistry and Physics)
The dynamical tropopause acts as a transport barrier between the tropical upper troposphere and extratropical lowermost stratosphere and is characterized by steep gradients in potential vorticity (PV) along an isentropic surface. Hence, the latitudinal separation between the dynamical tropopause in the Northern Hemisphere and Southern Hemisphere can be used as a metric of upper-tropospheric width for assessing climate change impacts. Here, we obtain the PV-gradient-based dynamical tropopause (PVG tropopause) from four meteorological satellite-era reanalyses (ERA5, ERA-Interim, JRA-55, MERRA-2) and investigate its climatology, variability and long-term trends from 1980 to 2017. Our results show a distinct seasonal cycle with larger PV values and a poleward movement of the PVG tropopause in summer. The climatological tropopause PV values are substantially different between different reanalyses, but the tropopause latitude is similar. Significant interannual variability in the PVG tropopause latitude is related to the El Niño–Southern Oscillation (ENSO) and weaker variability also to the quasi-biennial oscillation (QBO) and is consistently represented in reanalyses. In particular, El Niño correlates with equatorward shifts in the PVG tropopause and hence a decrease in upper-tropospheric width. Long-term trends in the PVG tropopause over the period 1980–2017 exhibit a distinct vertical structure with poleward shifts below 340 K potential temperature, equatorward shifts between 340 and 370 K, and poleward shifts between 370 and 380 K. This consistent widening at lower levels and narrowing in the upper troposphere also exhibit considerable zonal variability with the strongest upper-tropospheric narrowing over the eastern Pacific.